Adenomatoid odontogenic tumor with clear cell changes - Neeta Mohanty; Samapika Routray; Niharika Swain; Yashwant Ingale (Wolters Kluwer Medknow Publications, 2014)
Adenomatoid odontogenic tumor (AOT) has a limited biological profile and been an attention-grabbing tumor for a century for its origin. Though described earlier, it was widely accepted after Harbitz from Norway reported about this uncommon benign tumor in 1915. There has been a long debate as whether this tumor is a hamartoma or a neoplasm. Here, we present a case of AOT in a 20-year-old female with details of clinical, radiological and histological features along with clear cell changes, signifying AOT to be more aggressive in nature than assessed from earlier literature. Thus, we did an extensive search of PubMed literature on AOT with all its histopathological features associated until date to find the report of clear cell changes yet.